The impact of material properties, nutrient load and shear stress on biofouling in food industries - J. M. R. Moreira (2015)
In the food industry, biofilm formation in pipes, equipment and cooling systems increases maintenance costs, decreases operational efficiencies and is a source of contamination. Shear stress, nutrient load and surface material are important variables affecting the biofilm onset in industry. In this work, the combined impacts of these variables were assessed using three different materials (glass, copper and stainless steel), two nutrient loads (high and low nutrient medium) and two hydrodynamic conditions (static and dynamic). Initial adhesion and biofilm formation were studied in microplates using Escherichia coli as a model organism. Surface material was the factor with the strongest impact and adhesion/biofilm formation were correlated with surface hydrophobicity. However, the impact of this variable was dependent on the nutrient load and imposed shear stress. It was also found that, for the majority of the situations tested, initial attachment performance is a good predictor of biofilm formation behaviour and that the effects observed during attachment are amplified during biofilm maturation. Since shear stress is a major determinant in cell adhesion, the results of this study may find application in industrial systems operating at flow rates between 0.001 and 600 m(3) h(-1) depending on tube material and diameter.